2018
DOI: 10.1589/jpts.30.479
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pain scrambler therapy on the pain and quality of life of degenerative gonarthritis patients

Abstract: [Purpose] The purpose of this study was to identify the effects of pain scrambler therapy on the pain and quality of life of degenerative gonarthritis patients. [Subject and Methods] This study is a single case study. Pain scrambler therapy was applied for 40 minutes per session once a day for 15 days to a 62-year-old female patient diagnosed with degenerative gonarthritis. Pain was measured using the Visual Analogue Scale and quality of life was measured using the short form-36 item after therapy. [Results] D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Over that period, the SF-36 score increased from 79 to 95. [27] Kim et al described a case that showed an improvement in quality of life through the administration of ST in a patient suffering from shingles. This study aimed to analyse the effect of ST on antineuralgic pain and quality of life after shingles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over that period, the SF-36 score increased from 79 to 95. [27] Kim et al described a case that showed an improvement in quality of life through the administration of ST in a patient suffering from shingles. This study aimed to analyse the effect of ST on antineuralgic pain and quality of life after shingles.…”
Section: Discussionmentioning
confidence: 99%
“…[24] However, data on the effect of ST on quality of life, particularly among cancer patients, are more sketchy. [25][26][27][28] Therefore, this study intended to assess the effect of ST on the quality of life of patients suffering from thoracic and HNC. The secondary aim of this study was to understand the potential impact of quality of life by studying it along with evolutions in physical pain and morphine intake.…”
Section: Indian Journal Of Palliative Carementioning
confidence: 99%
“…Scrambler therapy has been used for several other chronic pain disorders for which isolated case reports are available including low back pain in which pain and depression was improved [74], arthritis of the knee with resulting improvement in pain and quality of life [75], and for paraneoplastic neuropathy and pruritus in which two patients were treated with very positive results [76].…”
Section: Other Isolated Case Reportsmentioning
confidence: 99%